LAPORAN ARUS KAS UNTUK PENINGKATAN KINERJA PERUSAHAAN - Andoko (MTU PRESS, 2024)
The purpose of this study is to determine how Tbk's financial performance is calculated using a cash flow statement. Field research, which involves observation, interviews, and library research involving the study of relevant literature, is the methodology employed in this study. Descriptive analysis, which explains the cash flow ratio as the foundation for the evaluation of financial performance, is the method used in this study. The study's findings demonstrate that, overall, the company's cash flow operating ratios are fairly good for each cash flow ratio, with the exception of the cash flow to total debt ratio, which has a low enough ratio to suggest that the company will not be able to pay off its debt with cash flow from operations.